RF Sputtering of Gold Nanoparticles in Liquid and Direct Transfer to Nafion Membrane for PEM Water Electrolysis - Chandrakanth Reddy Chandraiahgari; Gloria Gottardi; Giorgio Speranza; Beatrice Muzzi; Domenico Dalessandro; Andrea Pedrielli; Victor Micheli; Ruben Bartali; Nadhira Bensaada Laidani; Matteo Testi (Membranes)
Sputtering onto liquids is rapidly gaining attention for the green and controlled dry synthesis of ultrapure catalysts nanomaterials. In this study, we present a clean and single-step method for the synthesis of gold nanoparticles directly in polyethylene glycol (PEG) liquid using radio frequency (RF) magnetron sputtering and by subsequently transferring them to Nafion ionomer, fabricating a catalyst-coated membrane (CCM), an essential component of the proton exchange membrane water electrolyzer (PEMWE). The samples were systematically characterized at different stages of process development. The innovative transfer process resulted in a monodispersed homogeneous distribution of catalyst particles inside CCM while retaining their nascent nanoscale topography. The chemical analysis confirmed the complete removal of the trapped PEG through the process optimization. The electrochemical catalytic activity of the optimized CCM was verified, and the hydrogen evolution reaction (HER) in acidic media appeared outstanding, a vital step in water electrolysis toward H2 production. Therefore, this first study highlights the advantages of RF sputtering in liquid for nanoparticle synthesis and its direct application in preparing CCM, paving the way for the development of innovative membrane preparation techniques for water electrolysis.